UPAYA MENINGKATKAN HASIL BELAJAR DENGAN MENGGUNAKAN METODE COOPERATIVE LEARNING DALAM PEMBELAJARAN BAHASA INDONESIA DI SMA NEGERI 8 MERANGIN - Baitullah Baitullah (JUDIKA (JURNAL PENDIDIKAN UNSIKA), 2020)
This study aims to describe and find out the process of increasing the learning outcomes of learning Indonesian in the material discussing problems in news texts or articles of class X students of SMA Negeri 8 Merangin. This research is a classroom action research. The results of this study indicate that the cooperative learning model can increase student creativity both in the learning process and the results of achieving basic competencies in the material discussing news text problems or articles of class X students of SMA Negeri 8 Merangin. Completeness of student learning outcomes in the first cycle only reached 35.7% complete, this has not yet reached the level of research success, then was carried out again in the second cycle and obtained 85.7% of the 28 research samples, students who completed the learning.